Personalized microbiome‐based approaches to metabolic syndrome management and prevention: 使用基于微生物的个体化治疗方法来管理与预防代谢综合征. (2nd February 2017) - Shapiro, Hagit; Suez, Jotham; Elinav, Eran
Abstract: Personalized or precision medicine is a novel clinical approach targeted to the individual patient and based on integration of clinical, genetic, and environmental factors that define a patient uniquely from other individuals featuring similar clinical symptoms. Such a personalized medicine approach is increasingly applied for diagnosis, clinical stratification, and treatment of metabolic syndrome (MetS)‐associated risks and diseases, including obesity, type 2 diabetes, non‐alcoholic fatty liver disease, and their complications. One emerging factor that governs MetS manifestations is the microbiome, the composition, function, growth dynamics, associated metabolite profile and diverse effects of which on host immune and metabolic systems can all significantly affect metabolic homeostasis. Interindividual differences in microbiome composition and function, as well as personal variations in microbial‐derived products, pave the way towards microbiome‐based personalized medicine in treating MetS‐related diseases. Highlights: The microbiome plays pivotal roles in the pathogenesis of multiple manifestations of metabolic syndrome (MetS). Understanding the molecular mechanisms driving these effects will constitute an exciting challenge of microbiome research in the coming decade. As such, decoding how altered host–microbiome interactions effect MetS will enable the development of microbiome‐targeting approaches as means of personalized treatment of MetS. Variations in the microbiome mediate differential effects of the environment on metabolic homeostasis. Multiple host and environmental factors contribute to interindividual variations in the microbiome. This, in turn, leads to a person‐specific microbiome regulation of metabolic homeostasis. SCFA, short‐chain fatty acids; TMAO, trimethylamine‐ N ‐oxide; MetS, metabolic syndrome.